MEASURING THE EFFECTIVENESS OF INFORMATION SERVICES PROVIDED BY THE UNIVERSITY LIBRARIES - Jeyaraj, W.J (DEGREE OF MASTER IN LIBRARY AND INFORMATION SCIENCE, 2006)
Information is considered to be a basic resource for national development. Information plays a significant role in improving educational standards and quality of research. In higher educational institutions, particularly at the university level, these information needs are accomplished through university libraries. The ultimate goal of any library service is to ensure that the users are able to access the information for purposes for which they require it. Library should fulfill an information seeker by not just giving out the materials but with the self confidence and ability evolved in him or her. User satisfaction must be related with the performance of the information services. This study reveals to what extent especially the libraries of the Eastern University of Sri Lanka and the South Eastern University of Sri Lanka are contributing information services. The aim of the study is to measure the effectiveness of information services provided by the two university libraries. Except Non-academic staff, 40% of all the other staff has been selected and the students constitute 20%. In order to muster the data to measure the information service quality, structured questionnaires and observation have been utilized. The collected data have been presented in the form of tables, graphs and pie charts. These data were analyzed using univariate analysis which incorporate percentages, frequencies and five step Likert scale. This study has been analyzed under four major research dimensions as follows; Information Identification Services, Information Location Services, Information Document Delivery Services and Information Advisory Services.